Boosting English Proficiency Through Educaplay Games: Classroom Action Research Approach to Interactive Learning - Saputri, Avida Pramayshela (DAS Institute, 2025)
This research explores the effectiveness of Educaplay, an interactive digital platform, in enhancing English proficiency among 7th-grade students at SMP IPK Muhammadiyah Delanggu, specifically in the topic of describing people, under the Merdeka Curriculum. The study employed a Classroom Action Research (CAR) approach, involving 28 students over two learning cycles. Key areas of focus included vocabulary acquisition, grammar proficiency, and student engagement. Results indicated a 22% improvement in vocabulary acquisition and a 15% increase in grammar skills. Additionally, student engagement and participation rates rose from 68% in the first cycle to 90% in the second. Qualitative data from classroom observations, student feedback, and teacher interviews further supported the positive impact of Educaplay on classroom dynamics, collaborative learning, and motivation. These findings highlight the potential of gamified learning tools to foster an engaging, student-centered learning environment that aligns with modern curriculum standards. The study concludes by recommending broader adoption of digital platforms in language education to support interactive and effective learning experiences.